Prostate specific antigen concentration at age 60 and death or metastasis from prostate cancer: case-control study. (14th September 2010) - Vickers, Andrew J; Cronin, Angel M; Björk, Thomas; Manjer, Jonas; Nilsson, Peter M; Dahlin, Anders; Bjartell, Anders; Scardino, Peter T; Ulmert, David; Lilja, Hans
Abstract : Objective To determine the relation between concentrations of prostate specific antigen at age 60 and subsequent diagnosis of clinically relevant prostate cancer in an unscreened population to evaluate whether screening for prostate cancer and chemoprevention could be stratified by risk. Design Case-control study with 1:3 matching nested within a highly representative population based cohort study. Setting General population of Sweden taking part in the Malmo Preventive Project. Cancer registry at the National Board of Health and Welfare. Participants 1167 men aged 60 who provided blood samples in 1981 and were followed up to age 85. Main outcome measures Metastasis or death from prostate cancer. Results The rate of screening during the course of the study was low. There were 43 cases of metastasis and 35 deaths from prostate cancer. Concentration of prostate specific antigen at age 60 was associated with prostate cancer metastasis (area under the curve 0.86, 95% confidence interval 0.79 to 0.92; P<0.001) and death from prostate cancer (0.90, 0.84 to 0.96; P<0.001). The greater the number for the area under the curve (values from 0 to 1) the better the test. Although only a minority of the men with concentrations in the top quarter (>2 ng/ml) develop fatal prostate cancer, 90% (78% to 100%) of deaths from prostate cancer occurred in these men. Conversely, men aged 60 with concentrations at the median or lower (≤1 ng/ml) were unlikely to have clinically relevant prostate cancer (0.5% risk of metastasis by age 85 and 0.2% risk of death from prostate cancer). Conclusions The concentration of prostate specific antigen at age 60 predicts lifetime risk of metastasis and death from prostate cancer. Though men aged 60 with concentrations below the median (≤1 ng/ml) might harbour prostate cancer, it is unlikely to become life threatening. Such men could be exempted from further screening, which should instead focus on men with higher concentrations.